Graphic Imprints The Influence of Representation and Ideation Tools in Architecture - Marcos, Carlos L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This is the Proceedings of the International Congress of Graphic Design in Architecture, EGA 2018, held in Alicante, Spain, May 30-June 1, 2018. About 200 professionals and researchers from 18 different countries attended the Congress. This book will be of interest to researchers in the field of architecture and Engineering. Topics discussed are Innovations in Architecture, graphic design and architecture, history and heritage among others.
Papers will be organised according to the following topics: 1. DRAWING AND PROJECTS: Graphic ideation -- Graphic thinking -- Open form, parameterisation and algorithms -- Shape grammars -- 2. ARCHITECTURE AND RE-PRESENTATION: Architectural graphic narrative -- Surveys and revivals -- 3D modelling and rendering -- Digital surveys and tools -- 3. REPRESENTATION MATERIALITY AND DIGITAL FABRICATION: Models, representation and ideation -- Structural models and prototyping -- Digital fabrication -- C.A.A.D.-C.A.A.M. Synergies -- New Materiality -- 4. MAPPINGS, CITY AND TERRITORY: Cartographing landscape -- Urban Mapping -- Space Syntax, flows, and urban dynamisms -- 5. PROJECTIONS AND ARCHITECTURAL SPACE: Geometry and projections -- Spatial syntax and architectural topologies -- Reverse engineering -- 6. ARCHITECTURE, PHENOMENOLOGY, PERCEPTION AND INTERACTION: Perception and phenomenology -- Visual thinking and architecture -- Perception, orientation and cognition of architectural space -- Interaction and architecture -- Performative architecture -- 7. TEACHING INNOVATION AND RESEARCH: Analysis and architectural design -- Graphic representation, communication and narrative -- Geometry, projections and spatial visualization -- New technologies and digital processes.
Keywords: Engineering design; Graphic arts; Buildings -- Design and construction; Computer-aided engineering; Art -- Study and teaching; Engineering Design; Graphic Design; Building Construction and Design; Computer-Aided Engineering (CAD, CAE) and Design; Creativity and Arts Education